Testing Coconut Shell Liquid Smoke in Controlling the Pathogen Colletotrichum gloeosporioides that Causes Anthracnose Disease in Chili (Capsicum annum L.). - Naufal, Sari Magfirah; Rumahlewang, Wilhelmina; Tuhumury, Gratiana N C (Universitas Pattimura, 2023)
Colletotrichum gloeosporioides is a type of pathogen that causes anthracnose. This disease is classified as a major disease in chili plants which can cause great losses. Liquid smoke contains antimicrobial compounds, such as phenols and acids which effectively kill and inhibit pathogenic fungi. This study aimed to test the effectiveness of coconut shell liquid smoke in controlling C. gloeosporioides that cause anthracnose disease in chili plants. Observational variables in this study included the macroscopic and microscopic characteristics of the fungus, the diameter of the colony and the effectiveness of the inhibition. This study used coconut shell liquid smoke grade 1 sold commercially (A1), grade 2 liquid smoke sold commercially (A2), and grade 2 homemade liquid smoke (A3), with different dose levels, namely 0.5 ml (D1), 1.0 ml (D2) and 1.5 ml (D3), per 10 ml culture medium. The results of this study showed that coconut shell liquid smoke was effective in controlling C. gloeosporioides with a treatment dose of 1.0 ml or more for each type of liquid smoke, with an inhibition percentage of 100%.